Strategi Rekrutmen dalam Manajemen Sumber Daya Manusia - Ririn Puspita Rahmalia Putri; Sultan Zaki Kusuma; Candi Febri; Ken Maulana Kusnandar; Yofian Afrianto Pradana; Dewi Nuraini (Global Leadership Organizational Research in Management, 2025)
Effective recruits are key in human resource management (human resources) to achieving organizational goals. Good recruitment strategies not only attract qualified candidates but also ensure compliance between the needs of the company and the competence of prospective employees. The main focus lies in the importance of building strong branding to attract high-quality candidates. Moreover, the experience of the candidate during the recruiting process is important, where positive interaction can enhance the image of the company in the eyes of prospective employees. This research aims to explore and analyze effective recruiting strategies in human resource management. In a context of growing competition in the labor market, organizations need to adopt innovative recruiting methods to attract quality talents. The qualitative approach is used to further the best practices and challenges faced in the recruiting process. Data is collected through analysis of literature from credible sources. Research shows that the use of technology, such as digital platforms and social media, and an emphasis on organizational culture, is essential to attracting appropriate candidates. It is hoped that these findings may provide a guide to the company in formulating an adaptive and sustainable recruitment strategy, in support of the organization's growth and success.